2011
DOI: 10.1515/humr.2011.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of humor on memory: Is the humor effect about humor?

Abstract: Humorous material tends to be recalled at higher rates than non-humorous material however it is not clear why this occurs. The present study evaluated semantic elaboration, incongruity resolution, and perceived humor explanations of this memory phenomenon. Participants rated either inspirational or humorous properties of stimuli and recalled photographs, keywords and phrases. Results were most consistent with the perceived humor hypothesis. Participants' ratings of humor predicted recall performance even when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 21 publications
1
25
0
6
Order By: Relevance
“…However, a potential concern is that the disgust manipulation might also have affected the humorous qualities of the stories (Oppliger and Zillman, 1997;Rozin, Haidt and McCauley, 2008b;McGraw and Warren, 2010). Also humorous material tends to be recalled at higher rates (Carlson, 2011). We therefore decided to investigate whether the manipulation had affected the humorous qualities, and whether this could explain the anomalous results for the dog story (Experiment 2 below).…”
Section: Discussionmentioning
confidence: 99%
“…However, a potential concern is that the disgust manipulation might also have affected the humorous qualities of the stories (Oppliger and Zillman, 1997;Rozin, Haidt and McCauley, 2008b;McGraw and Warren, 2010). Also humorous material tends to be recalled at higher rates (Carlson, 2011). We therefore decided to investigate whether the manipulation had affected the humorous qualities, and whether this could explain the anomalous results for the dog story (Experiment 2 below).…”
Section: Discussionmentioning
confidence: 99%
“…The retrieval processes of memory this effect can be observed in the Incongruity Resolution Hypothesis posited by Carlson (2011). The resolution of semantic incongruities associated with humor creates a memory advantage for the humorous material, resulting in advantaged recall and enduring memory for the material (Carlson, 2011). In the study, Carlson (2011) found it was not necessary for students to intentionally process humor in order for the humor effect to emerge.…”
Section: Benefits Of Humor Usagementioning
confidence: 80%
“…The resolution of semantic incongruities associated with humor creates a memory advantage for the humorous material, resulting in advantaged recall and enduring memory for the material (Carlson, 2011). In the study, Carlson (2011) found it was not necessary for students to intentionally process humor in order for the humor effect to emerge. This may be encouraging to instructors in that students may not necessarily need to fully comprehend the experienced.…”
Section: Benefits Of Humor Usagementioning
confidence: 81%
See 1 more Smart Citation
“…Humor has been found to affect memory in both intentional and incidental humorous memory situations (Carlson, 2011), meaning students' retention of material is positively affected by classroom humor whether or not it was intentional on the part of the instructor. The perception of humor remains an important component in the humor-memory relationship.…”
Section: Humor Enhanced Memory and Information Retentionmentioning
confidence: 99%